2018
DOI: 10.1097/pec.0000000000001014
|View full text |Cite
|
Sign up to set email alerts
|

Genital and Extragenital Gonorrhea and Chlamydia in Children and Adolescents Evaluated for Sexual Abuse

Abstract: Positive tests for NG and CT in patients evaluated for sexual victimization may represent infection from sexual contact, contiguous spread of infection, or the presence of infected assailant secretions. Relying on patient reports of symptoms, or types of sexual contact, to determine need for testing may miss NG and CT infections in patients evaluated for sexual victimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 21 publications
0
11
0
3
Order By: Relevance
“…6 A few previous studies of adolescents and adults have reported gonorrhea and chlamydia infections isolated from extragenital sites using NAAT testing. 8,9 In a recent study 10 of 1319 children and adolescents who presented for acute and nonacute assessments for sexual abuse/assault and were tested for gonorrhea and chlamydia, 120 had at least 1 positive NAAT from a genital or extragenital (oral, anal) site. Most patients who tested positive for gonorrhea or chlamydia did not have genital discharge and most who had positive results from extragenital sites did not provide a history of contact at that site.…”
Section: Testing For Sexually Transmitted Infectionsmentioning
confidence: 99%
“…6 A few previous studies of adolescents and adults have reported gonorrhea and chlamydia infections isolated from extragenital sites using NAAT testing. 8,9 In a recent study 10 of 1319 children and adolescents who presented for acute and nonacute assessments for sexual abuse/assault and were tested for gonorrhea and chlamydia, 120 had at least 1 positive NAAT from a genital or extragenital (oral, anal) site. Most patients who tested positive for gonorrhea or chlamydia did not have genital discharge and most who had positive results from extragenital sites did not provide a history of contact at that site.…”
Section: Testing For Sexually Transmitted Infectionsmentioning
confidence: 99%
“…This is important since the individual could serve as a reservoir for ongoing transmission cycles, especially with increasing reports of oral-genital sexual practice among adolescents (23,24). A recent study in children evaluated for sexual victimization showed that C. trachomatis and N. gonorrhoeae can be detected in anatomic sources where no prior sexual contact was reported (12). A comprehensive screening practice for C. trachomatis and N. gonorrhoeae with a history or suspicion of recent sexual contact could aid in diagnosis of STI.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, data from an evidencebased systematic review showed that in children younger than 12 years of age, most of the cases of C. trachomatis (75 to 94%) and N. gonorrhoeae (36 to 85%) infections were linked to sexual assault (25). A recent study in children and adolescents being evaluated for sexual abuse shows that C. trachomatis infection and gonorrhea were detected in extragenital sites (oropharynx and rectum), even when sexual contact with the abuser's genitals was not reported (12). A recent study showed that appropriate STI testing, including for C. trachomatis and N. gonorrhoeae in extragenital sites was done only for 5% of adolescents presenting to the emergency department with oropharyngeal or anorectal chief complaints (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…American Academy of Pediatrics, yüksek sensitivetisi ve kültüre yakın spesifitesi nedeniyle bu etkenlerin saptanmasında NAAT'ni önermektedir. Ayrıca son yıllarda yapılmış çalışmalarda, cinsel istismar sonrası ekstragenital örneklerde de NAAT'nin kullanılabileceği bildirilmektedir (47,48).…”
Section: B3 Etken Taraması Ve Tanı Testleriunclassified